Problem-based Learning in Computer-assisted Translation Pedagogy - Mellinger, Christopher D. (HERMES - Journal of Language and Communication in Business, 2018)
This article discusses problem-based learning (PBL) and its potential application to computer-assisted translation (CAT) pedagogy. Problem-based learning is situated in the CAT classroom as a final course component in which students challenge their previously-acquired knowledge and skill sets to solve unique, ill-defined problems that mirror those encountered in the language industry. This constructivist approach to education is designed to empower students to be self-directed, collaborative learners and to foster critical thinking and reflection. Moreover, problem-based learning is a means to encourage professional behavior and to develop skills beyond the mere use of translation technologies. This article explores the potential advantages and disadvantages of this educational approach as documented in related professional fields. In addition, the article addresses the ways in which problems are designed and implemented in the translation classroom, with a discussion of how they can and should be aligned with course learning objectives. The article concludes with a discussion of ways students’ work ought to be assessed to enhance gains often seen in PBL environments.